Macular outer nuclear layer, ellipsoid zone and outer photoreceptor segment band thickness, axial length and other determinants - Wang, Ya Xing; Pan, Zhe; Xue, Can Can; Xie, Hui; Wu, Xiaodong; Jonas, Jost B. (Scientific reports, 2023)
The study aims to assess the thickness of the retinal outer nuclear layer (ONL), ellipsoid zone (EZ) and photoreceptor outer segment (POS) band in various macular regions and its associations with axial length and other parameters. Participants of the Beijing Eye Study 2011 underwent a series of examinations including spectral-domain optical coherence tomography of the macula. The current study included 2213 participants without retinal or optic nerve diseases (age: 61.7 ± 8.4 years; range 50-93 years); axial length: 23.15 ± 0.95 mm; range 18.96-29.15 mm). The ONL (fovea: 98.9 ± 8.8 µm), EZ (fovea: 24.1 ± 0.5 µm) and POS band (fovea: 24.3 ± 3.5 µm) were the thickest (P < 0.001) in the fovea (defined as the thinnest central point), followed by the temporal inner, nasal inner, inferior inner, superior inner, inferior outer, temporal outer, nasal outer, and superior outer region. In multivariable analysis, a thicker retinal ONL was associated (correlation coefficient r: 0.40) with shorter axial length (beta: − 0.14; P < 0.001) and shorter disc-fovea distance (beta: − 0.10; P = 0.001), after adjusting for younger age (beta: − 0.26; P < 0.001), male sex (beta: 0.24; P < 0.001), lower serum cholesterol concentration (beta: − 0.05; P = 0.04), and thicker subfoveal choroidal thickness (beta: 0.08; P < 0.001). The POS thickness increased with shorter axial length (beta: − 0.06; P < 0.001) and shorter optic disc-fovea distance (beta: − 0.05; P = 0.03), after adjusting for younger age (beta: − 0.34; P < 0.001), male sex (beta: 0.15; P < 0.001), and thicker subfoveal choroidal thickness (beta: 0.24; P < 0.001). As a conclusion, the photoreceptor ONL, EZ and POS band vary in thickness between different macular regions and differ in their correlations with axial length, disc-fovea distance, age, sex, and subfoveal choroidal thickness. The ONL thickness decrease with longer axial length and longer disc-fovea distance may point to an axial elongation-associated retinal stretching in the macula.